The psychological burden of an initially unexplained illness: patients with sternocostoclavicular hyperostosis before and after delayed diagnosis - Chotkan Sadhna A (Health and Quality of Life Outcomes, 2010)
Abstract Background Sternocostoclavicular hyperostosis (SCCH) is a rare, debilitating, chronic inflammatory disorder of the anterior chest wall due to a chronic sterile osteomyelitis of unknown origin. SCCH is largely underdiagnosed and often misdiagnosed. In individual cases it can remain unrecognized for years. The purpose of this study is twofold. Firstly, to evaluate the psychological condition of SCCH patients, both in the sometimes quite extended pre-diagnostic period between first manifestations and confirmed diagnosis of the disease, and in the current situation. Secondly, to investigate the relationships between the pre-diagnostic and the current psychological conditions of confirmed SCCH patients. Methods Structured interviews were held with 52 confirmed SCCH patients. Questionnaires were included to assess posttraumatic stress symptoms, social support, aspects of pain, illness perceptions, self-reported health status, and quality of life. Results SCCH patients reported stronger posttraumatic stress symptoms, more unfavorable illness perceptions, lower health status, and poorer quality of life than healthy individuals and patients with other diseases or traumatic experiences. Psychological distress in the pre-diagnostic period was associated with unfavorable conditions in the current situation. Conclusion SCCH is an illness with serious psychological consequences. Psychological monitoring of patients with unexplained complaints is recommended as long as a diagnosis has not been reached.